2022
DOI: 10.1002/qj.4257
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stochastically perturbed parametrisation tendencies (SPPT) on rapidly ascending air streams

Abstract: The stochastically perturbed parametrisation tendency (SPPT) scheme is a well-established technique in ensemble forecasting to address model uncertainty by introducing perturbations into the tendencies provided by the physics parametrisations. The magnitude of the perturbations scales with the local net parametrisation tendency, resulting in large perturbations where diabatic processes are active. Rapidly ascending air streams, such as warm conveyor belts (WCBs) and organized tropical convection, are often dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Moreover, it could be related to the representation of microphysical processes. Pickl et al (2022) showed that ECMWF's stochastically perturbed parameterisation tendency (SPPT) scheme systematically increases the number of rapidly ascending airstreams, although the SPPT perturbations are symmetric around zero (a similar behavior has recently been found for the stochastically perturbed parametrisations (SPP) scheme, which is currently under development at ECMWF: Deinhard & Grams, 2023). As rapidly ascending airstreams play an important role for cyclone intensification (e.g., Binder et al, 2016), the SPPT could thus contribute to a higher maximum cyclone intensity through the same mechanism.…”
Section: Year-round Overestimation Of Maximum Cyclone Intensitymentioning
confidence: 99%
“…Moreover, it could be related to the representation of microphysical processes. Pickl et al (2022) showed that ECMWF's stochastically perturbed parameterisation tendency (SPPT) scheme systematically increases the number of rapidly ascending airstreams, although the SPPT perturbations are symmetric around zero (a similar behavior has recently been found for the stochastically perturbed parametrisations (SPP) scheme, which is currently under development at ECMWF: Deinhard & Grams, 2023). As rapidly ascending airstreams play an important role for cyclone intensification (e.g., Binder et al, 2016), the SPPT could thus contribute to a higher maximum cyclone intensity through the same mechanism.…”
Section: Year-round Overestimation Of Maximum Cyclone Intensitymentioning
confidence: 99%
“…Further, Pickl et al . (2022) found sensitivities of WCBs to stochastic perturbations of physical processes. This indicates that WCBs can act as a direct source of forecast uncertainty, additionally to the propagation and amplification of pre‐existing forecast errors through upscale error growth.…”
Section: Introductionmentioning
confidence: 99%
“…As the scale of cloud microphysical processes responsible for precipitation formation is too small to be explicitly resolved in NWP models, parameterizations are used to calculate the integrated effects on the resolved prognostic variables. These parameterization schemes, however, are still associated with large uncertainties that can influence the representation of atmospheric dynamics including airmass ascent and formation of precipitation in NWP models (Leutbecher and Palmer, 2008;Ollinaho et al, 2017;Pickl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%